Kepatuhan Perpajakan dalam Praktik Sehari-hari - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
Tax compliance is a fundamental aspect in ensuring sustainable state revenue and supporting national development. In daily practice, tax compliance is not only reflected in the fulfillment of formal obligations such as tax reporting and payment, but also in taxpayers’ awareness, attitudes, and behavior toward taxation regulations. This study aims to examine tax compliance in daily practices and to identify factors that influence taxpayer compliance. This research employs a descriptive qualitative method using a literature study approach. Data were collected from textbooks, scientific journals, official reports issued by the Directorate General of Taxes, and relevant taxation regulations. The analysis was conducted by reviewing and synthesizing findings from previous studies related to taxpayer compliance, taxpayer behavior, and taxation administration systems. The results indicate that tax compliance in daily life is influenced by several interrelated factors, including taxpayers’ understanding of tax regulations, perceptions of tax fairness, quality of tax services, and the effectiveness of tax administration systems. The implementation of digital tax systems, such as e-filing and e-billing, has contributed to improving formal compliance by simplifying administrative procedures. However, digitalization has not fully enhanced material compliance due to limitations in tax literacy and digital access among taxpayers. The study concludes that improving tax compliance requires a comprehensive approach that combines regulatory enforcement with educational and persuasive strategies. Enhancing tax literacy, improving service quality, and increasing transparency in tax management are essential to fostering voluntary compliance. Strengthening taxpayer trust in the taxation system is expected to support sustainable tax compliance in the long term.